Preliminary Findings of mRNA Covid-19 Vaccine Safety in Pregnant Persons. Issue 4 (December 2021) - Shimabukuro, T.T.; Kim, S.Y.; Myers, T.R.; Moro, P.L.; Oduyebo, T.; Panagiotakopoulos, L.; Marquez, P.L.; Olson, C.K.; Liu, R.; Chang, K.R.; Ellington, S.R.; Burkel, V.K.; et al.
Abstract : ( New Engl J Med . 2021;384:2273–2282) When the Moderna and Pfizer-BioNTech COVID-19 vaccines were granted Emergency Use Authorization by the Food and Drug Administration in December 2020, there was limited data concerning the safety of these vaccines during pregnancy. Pregnant individuals with COVID-19 are at higher risk for severe illness, death and adverse pregnancy outcomes. The Centers for Disease Control and Prevention (CDC) and other organizations have indicated that pregnant people can receive the COVID-19 vaccines. Monitoring pregnant individuals who have received the COVID-19 vaccines, and establishing safety profiles is important to inform future recommendations. This study reports on preliminary data on COVID-19 vaccine safety in pregnant patients.